Money, mandates, and local control in American public education - Shelly, Bryan (University of Michigan Press, 2011)
"'This book is outstanding. . . . No one has delved into the issue of school financing with such depth, data and thoughtful analysis. It is simply the best in the field.' Susan B. Neuman, University of Michigan Pointing to the disparities between wealthy and impoverished school districts in areas where revenue depends primarily upon local taxes, reformers repeatedly call for the centralization of school funding.Their proposals meet resistance from citizens, elected officials, and school administrators who fear the loss of local autonomy.Bryan Shelly finds, however, that local autonomy has already been compromised by federal and state governments, which exercise a tremendous amount of control over public education despite their small contribution to a school systems funding. This disproportionate relationship between funding and control allows state and federal officials to pass education policy yet excuses them from supplying adequate funding for new programs. The resulting unfunded and underfunded mandates and regulations, Shelly insists, are the true cause of the loss of community control over public education. He demonstrates the effects of the most infamous of underfunded federal mandates, the No Child Left Behind Act of 2001 (NCLB), and explores why schools implemented it despite its unpopularity and out-of-pocket costs. Shellys findings hold significant implications for school finance reform, NCLB, and the future of intergovernmental relations."--